Anti-infection healing-promoting alginate dressing

By introducing a composite structure of an antibacterial barrier layer, an alginate multifunctional layer and a one-way guide wet layer into the alginate dressing, combined with materials such as bioactive glass and nano ZnO, the shortcomings of existing dressings in promoting wound healing and preventing infection are solved, and low-cost and efficient anti-infection and pro-healing effects are achieved.

CN119633158AActive Publication Date: 2025-03-18LINYI KANGLI MEDICAL DEVICES CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411891293.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Existing alginate dressings have shortcomings in promoting wound healing and preventing infection, especially in terms of cost and function, which are difficult to meet clinical needs.

Method used

Using a composite structure of an antibacterial barrier layer, an alginate multifunctional layer and a one-way wet guide layer, PCL/alginate composite fiber membranes are prepared through electrospinning technology, and combined with bioactive glass, nano ZnO and other materials to form a dressing with dual functions of anti-infection and promoting healing.

Benefits of technology

It achieves efficient anti-infection and promotes wound healing, and is low-cost, and is suitable for various wound care, especially the treatment of refractory wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633158A_ABST
    Figure CN119633158A_ABST
Patent Text Reader

Abstract

The invention provides an anti-infection healing-promoting alginate dressing, and belongs to the technical field of medical dressings. The dressing comprises an antibacterial barrier layer, an alginate multifunctional layer and a one-way moisture conducting layer which are sequentially arranged, the antibacterial barrier layer is a PCL / alginate (SA) film, the alginate multifunctional layer contains bioactive glass, nano ZnO, alginate dressing and other components, the one-way moisture conducting layer is a PCL film, and all the surface layers are compounded into a whole through a hot pressing process. According to the invention, a formula of the multifunctional alginate dressing with excellent performance is constructed, a compounding process of each layer of material is designed, and meanwhile, pores of the antibacterial barrier film are controlled. The alginate dressing and the bioactive glass are combined, the double functions of healing promotion and infection resistance are achieved, the effect is outstanding, the dressing body is free of medicine components, and use is safe and reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical dressings, in particular to an anti-infection and healing-promoting alginate dressing. Background Art

[0002] Alginate is a natural polysaccharide carbohydrate extracted from seaweed, which has excellent biocompatibility and biodegradability, which makes alginate dressings have broad application prospects in the field of biomedical materials. As a functional wound dressing, alginate dressings have multiple functions such as absorbing exudate, promoting wound healing, and preventing infection. The realization of these functions depends on its unique chemical structure and physical properties, such as high hygroscopicity, hemostasis, and gelation.

[0003] The wide application prospects of alginate dressings in the field of wound care are remarkable. They are not only suitable for general wound care such as skin trauma, burns, ulcers, etc., but can also be extended to the treatment of refractory wounds such as diabetic foot, venous ulcers, bedsores, etc. In addition, with the continuous development of biomedical technology, polysaccharide dressings may also be combined with other treatment methods (such as gene therapy, stem cell therapy, etc.) to provide a more comprehensive and effective solution for wound care.

[0004] In current medical practice, there is a widespread demand for dressings that can effectively promote wound healing and prevent infection. Wound dressings play an important role in the healing process. Nowadays, zinc alginate, calcium alginate and sodium alginate are commonly used as alginate complexes in clinical practice. Although calcium alginate dressings can achieve hemostasis, they have no additional effects, such as antibacterial properties or accelerated wound healing. Therefore, it is very necessary to develop wound dressings that can adapt to wounds, are non-toxic, biocompatible, antibacterial, moisturizing, have appropriate adhesion (will not adhere to tissue when removed), can promote skin regeneration to accelerate wound healing, and are low-cost. Summary of the invention

[0005] The technical problem to be solved by the present invention is: how to develop a wound dressing with better performance.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: An anti-infection and healing-promoting alginate dressing, comprising an antibacterial barrier layer, an alginate multifunctional layer, and a unidirectional moisture-conducting layer; The antibacterial barrier layer is prepared by the following method: 1) SA was dissolved in deionized water to prepare a SA aqueous solution of a certain concentration, and the solution was allowed to stand for degassing. Chloroform, SA aqueous solution and Span80 were homogenized in a homogenizer at a speed of 7000 r / min for 15 min according to the proportion, and PCL was then added. The solution was placed on a constant temperature shaker for continuous homogenization for 12 h. After PCL was completely dissolved, the homogenizer was homogenized at a speed of 7000 r / min for 15 min to obtain a spinning emulsion. The ratio of PCL mass to SA aqueous solution volume was 1 g: 1 ml, and the mass fraction of Span80 relative to PCL was 66%. 2) The emulsion is subjected to electrospinning to prepare a SA / PCL composite fiber membrane; wherein the spinning solution flow rate is 0.65 ml / h, the spinning voltage is 10.5 kV, the receiving distance is 10 cm, the spinning environment temperature is 25±5° C., and the relative humidity is 60±5%; The unidirectional moisture conducting layer is prepared by the following method: A) PCL was dissolved in medical acetone at a mass fraction of 1:4 and stirred at room temperature for 4 h using a magnetic stirrer to obtain a solution; B) Electrospinning was performed on it. During the electrospinning process, the solutions were poured into 5 ml syringes respectively and installed on the electrospinning equipment in turn for spinning; a needle with an inner diameter of 0.41 mm was used, the spinning voltage was 15 kV, the flow rate was 1 mL / h, the distance between the needle and the collector was 15 cm, and a rotating drum at 300 rpm was used as the collector; the prepared samples were dried in a drying oven and stored in a refrigerator at 4°C.

[0007] Preferably, the alginate multifunctional layer is a bioactive glass / nano ZnO / alginate dressing, and the bioactive glass / nano ZnO / alginate dressing is prepared by the following method: A) Add 12.2 mL of LTEOS and 7.8 g of Ca(NO3)2·4H2O to a solution of 120 mL of deionized water and 40 mL of anhydrous ethanol, adjust the pH value of the solution to 1.8-2.2 with hydrochloric acid while stirring, then dissolve 1.3 g of (NH4)2HPO4 in deionized water, add polyethylene glycol (PEG-10000) after it is completely dissolved, stir well and pour into the above solution, add ammonia water to adjust the pH to 10, stir for 48 h, then place in air for aging for 24 h to obtain a white precipitate, place the precipitate in a freeze dryer for freeze drying, and then place it in a box-type electric furnace for heat treatment at a sintering temperature of 650°C to obtain nanoscale bioactive glass; B) Spherical ZnO nanoparticles were synthesized by mixing 0.1 M zinc acetate dihydrate and 0.025-0.2 M sodium hydroxide in methanol. During the synthesis, polyethylene glycol was used as a surfactant and the reaction mixture was stirred at room temperature for 20 min, wherein the amount of PEG added was 0.08-0.12 g PEG per gram of ZnO. The precipitate was washed several times with ethanol and deionized water, and then redispersed in deionized water using ultrasound. C) According to the weight ratio, 2-5 parts by weight of sodium alginate, 0.5-1 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and 0.5-1 parts by weight of N-hydroxysuccinimide are added in a certain molar ratio to 100-200 parts by weight of a phosphate buffer solution with a pH of 6-7, stirred evenly, and then added to 50-100 parts by weight of a methanol solution containing dodecylamine, stirred at room temperature for 12-24 hours, then precipitated with methanol, centrifuged, dissolved with distilled water, dialyzed for 48-96 hours, and freeze-dried to obtain hydrophobically modified sodium alginate; D) Sodium alginate is completely dissolved in distilled water to form a 10% to 15% alginate solution as a spinning solution, the spinning solution is poured into a syringe, the other end of which is connected to a nitrogen bottle, and squeezed into a 5% to 10% calcium chloride solution under nitrogen pressure for a coagulation bath, and the gel-like fibers derived from the coagulation bath are stretched, washed, wound, and dried to obtain calcium alginate fibers; E) Adding bioactive glass to a mixture of water and ethanol, and uniformly dispersing the powder to form a suspension, wherein the volume ratio of water to ethanol in the mixture is 1:1; mixing ZnO nanoparticles with a concentration of 0.5% with the suspension to uniformly disperse the particles; immersing hydrophobically modified calcium alginate fibers in saturated KMnO4 for 5-10 minutes, and then washing with distilled water to obtain de-roughened alginate fibers; immersing the de-roughened alginate fibers in the suspension and fully soaking them, and uniformly spraying the suspension on the fiber surface, and then centrifuging and dehydrating the fibers, soaking the obtained wet fibers in an ethanol solution, centrifuging to remove the ethanol, drying them naturally, and then vacuum drying them at 60-80°C, and then cutting the dried fibers into short fibers, sterilizing them after a non-woven fabric processing process.

[0008] Preferably, the alginate multifunctional layer is a bioactive glass / chitosan / alginate dressing, and the bioactive glass / chitosan / alginate dressing is prepared by the following method: A) Take 12.5g TEP, 8.5g CN, and 1.46g TEOS, and drop TEOS and TEP into a hydrochloric acid aqueous solution in sequence, continue stirring for 1h after the addition is completed, then add solid CN to the solution in multiple times, continue stirring the solution after the addition is completed to fully hydrolyze the precursor, and stop when the solution becomes transparent and uniform; let the obtained sol solution stand for aging at room temperature for 3 days, and place the gel at 60°C and 120°C for 3 days respectively; put the dried gel into a high-temperature sintering furnace for sintering treatment; put the obtained sintered product, agate grinding balls, and anhydrous ethanol into a ball mill at a mass ratio of 1:3:1 and ball mill on a ball mill; after the ball milling is completed, place the ball milling liquid in a 120°C oven and dry it for one day; sieve the obtained powder with a 20-50 micron standard sieve to obtain SGBG powder; and mix the SGBG at a solid-liquid ratio of 80-150 g / 200-500 ml. The powder is dispersed in acetone, and ultrasonic vibration treatment and mechanical stirring are applied simultaneously to obtain a bioactive glass dispersion; B) preparing an acetic acid aqueous solution containing chitosan, wherein: the ratio of the mass of chitosan to the volume of the acetic acid aqueous solution is 1-3 g:100 mL; uniformly mixing the acetic acid aqueous solution containing chitosan and a sodium alginate aqueous solution, wherein: the mass fraction of acetic acid in the acetic acid aqueous solution is 1%, the sodium alginate aqueous solution is prepared by mixing sodium alginate and ultrapure water, and the ratio of the mass of sodium alginate to the volume of ultrapure water is 0.5-1.5 g:50 mL; then adding an aqueous solution of a bioactive glass suspension to obtain a mixture, wherein: the bioactive glass suspension is prepared by mixing bioactive glass and ultrapure water, and the ratio of the mass of the bioactive glass to the volume of the ultrapure water is 0.2-0.6 g:2 mL; C) The spinning solution of sodium alginate is used to make silk, the silk is drawn and washed, and then soaked in a solution or suspension containing a wound healing promoting drug, and then dried, wound and cut into sodium alginate fibers, and the sodium alginate fibers are opened, combed and reinforced with needle punching or hydroentanglement with or without cross-lapping.

[0009] Preferably, the sintering conditions in step a) are: heating rate 1°C / min; during heating from room temperature to 600°C, keeping at 350°C and 600°C for 120 min each; ball milling parameters: 672 rpm, 4 h.

[0010] Preferably, the alginate multifunctional layer is a copper-containing mesoporous bioactive glass / honey / alginate dressing, and the copper-containing mesoporous bioactive glass / honey / alginate dressing is prepared by the following method: A) 6.92 g Pluronic F108 was dissolved in 36.2 ml ethanol in a 40°C water bath to obtain solution I, 2.48 g Ca(NO3)24H2O, 0.637 g TEP, 11.66 g TEOS, 1.9 ml 1M HCl, 15.24 ml ethanol and 5.72 ml H2O were fully mixed under stirring to obtain solution II; solution I and solution II were mixed in a container, and stirred overnight in a sealed container in a 40°C water bath; the sol was then poured into a petri dish and subjected to EISA treatment in a 40°C room temperature water bath; the obtained gel was placed at 40°C for 6 days to age; the collected dry gel was then calcined at 600°C for 5 hours, and then ground using a desktop planetary ball mill to obtain MBGs fine powder; B) by weight, 50-100 parts of honey are decrystallized and liquefied at 65-80°C, and then low-temperature dehydrated until the water content of the honey is 15%-25%, and then 0.5-3 parts of synthetic borneol are added to stir and mix well, and the mixture is placed in a freeze dryer for freeze drying at -40--10°C for 12-36 hours, and then taken out to form solid honey, and then the solid honey layer is crushed into honey powder of 60 meshes to 500 meshes; C) MBGs fine powder was gradually added to distilled water, the suspension was dispersed in an ultrasonic probe for 2 min, honey was added to it, and subsequently, the honey / SA / PVA mixture was stirred at room temperature for 12 h to obtain a homogeneous solution; 1.5% w / v CMC and alginate separation solutions were prepared in distilled water; the two solutions were kept at 50 °C under magnetic stirring until the mixture was homogenized within 30 min; 5%, 7.5% and 10% w / v glycerol were added to each solution respectively; 1% CaCl2 aqueous solution was prepared and dropped into the alginate solution while it was still stirred and heated; after obtaining the two membrane solutions, they were mixed at a mass ratio of 1:1 under mechanical stirring at 900 rpm for 30 min; then the solutions were heated at 0.28 g / cm 2 The solution was poured into an acrylic plate under standard conditions and kept in a circulating air oven at 40°C for 24 hours; after the solution dried, the obtained dressing was immersed in an aqueous solution of 5% calcium chloride and 3% glycerol for 20 minutes; the dressing was then immersed in a 3% glycerol aqueous solution for 1 minute for washing.

[0011] Preferably, in step a), the Si:Ca:P molar ratio of the MBGs fine powder is 80:15:5.

[0012] Preferably, in step A), solution II further contains copper (II) nitrate hemihydrate (pentahydrate), and the obtained MBGs fine powder has a Si:Cu:Ca:P molar ratio of 78:2:15:5 or 75:5:15:5.

[0013] Preferably, the anti-infection and healing-promoting alginate dressing is prepared by the following method: the electrospun membrane and the non-woven fabric are laminated using a temperature and pressure controllable lamination device, during which the materials are arranged in the structural order of the antibacterial barrier layer, the alginate functional layer and the unidirectional moisture conducting layer; during the lamination process, the equipment is set to work at a lamination temperature of 56°C and a pressure of 12N, and the lamination time is controlled at 40 seconds.

[0014] Preferably, the preparation method of the antibacterial barrier layer is replaced by the following method: 1) 3.6% PCL and 2.4% SA were dissolved in TFE and stirred continuously for 24 h. ICA and MXF with a mass ratio of 0.05 and 5 wt% were added to the polymer solution, respectively, and stirred for 24 h to prepare electrospinning solutions containing the corresponding drugs. The solutions containing ICA and MXF were assembled into PCL / alginate membranes by electrospinning. 2) The electrospinning solution containing ICA was heated at 1.0 mL h −1 The material was fed through a blunt needle at a rate of 22 kV; the voltage was 22 kV, the distance between the needle and the grounded mandrel was 20 cm, and the rotation speed was 500 rpm; at 25 °C, the electrospinning was terminated after 4 h, and the solution containing MXF was electrospun for another 4 h under the same electrospinning parameters.

[0015] The present invention provides an anti-infection and healing-promoting alginate dressing. This technical solution uses a multifunctional dressing that combines alginate, PCL (polycaprolactone), bioactive glass, nano ZnO, etc., which has the dual functions of anti-infection and healing. Alginate, as the main component, effectively absorbs and retains wound exudate with its excellent water absorption and biocompatibility, maintains a moist environment and promotes healing. PCL, as a supporting structural material, not only enhances the mechanical strength and stability of the dressing, but also ensures the comfort and long-term effect of the dressing during use. Bioactive glass, as an anti-infection and healing-promoting component, effectively inhibits the growth of pathogens and stimulates tissue regeneration. This innovative formula design not only focuses on the interaction and optimization of functional materials, but also achieves the optimal balance of the dual functions of anti-infection and healing through structural design.

[0016] In terms of the composite process of each layer of materials, the present invention uses electrospinning technology to prepare three layers of materials (antibacterial barrier membrane: PCL + alginate, alginate dressing, unidirectional moisture-conducting layer: PCL), and uses a hot pressing process for composite. Hot pressing not only ensures good adhesion and bonding between the layers of materials, but also ensures the structural stability and functional integrity of the final product. Through this composite process, innovative multifunctional alginate dressings are realized.

[0017] In addition, the present invention effectively controls the pores of the antibacterial barrier membrane. The barrier membrane is composed of PCL and alginate, and its purpose is to prevent the entry of external bacteria. The process parameters of electrospinning need to be precisely controlled to make the pores of the barrier membrane as small as possible. Its main purpose is to effectively block external bacteria, thereby reducing the risk of infection. In the electrospinning preparation process, it is crucial to accurately control the process parameters to ensure that the pores of the barrier membrane are as small as possible. In order to achieve precise control of the pore size, it is necessary to optimize key parameters such as the concentration of the spinning solution, the electric field strength, and the spinning speed. Higher solution concentrations and appropriate electric field strengths can make the fibers thinner and more closely arranged, thereby reducing the pore size.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Composite functional innovation: combining alginate dressing with bioactive glass to achieve dual functions of promoting healing and anti-infection 2. Drug-free dual-function dressing: The main body of the dressing uses drug-free ingredients to achieve the dual functions of promoting healing and resisting infection.

[0019] 3. Single-substance dual-function dressing: Only the same substance is used to achieve the dual functions of promoting healing and anti-infection. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic structural diagram of the dressing of the present invention.

[0021] Figure 2 This is a flow chart of the preparation of the sol-gel bioactive glass (BG-1) in the present invention. DETAILED DESCRIPTION

[0022] The specific embodiments of the present invention will be described in detail below. In order to avoid too much unnecessary details, the well-known structures or functions will not be described in detail in the following examples. The approximate language used in the following examples can be used for quantitative expression, indicating that the quantity can be allowed to have a certain change without changing the basic function. Unless otherwise defined, the technical and scientific terms used in the following examples have the same meaning as those generally understood by those skilled in the art to which the present invention belongs.

[0023] An anti-infection and healing-promoting alginate dressing, such as Figure 1 As shown, it includes an antibacterial barrier layer, an alginate multifunctional layer, and a unidirectional moisture conducting layer.

[0024] (1) Materials and preparation of antibacterial barrier layer Preparation method of PCL / alginate (SA) membrane 1: 1. Preparation of SA / PCL emulsion There are two methods for preparing emulsions: the two-step method, in which the dispersed phase is prepared first, added to a solvent containing a surfactant, and after it is fully dispersed, the continuous phase polymer is added to dissolve and disperse again. The one-step method, in which the dispersed phase and the continuous phase are prepared separately, and then the dispersed phase is added to the continuous phase containing a surfactant and fully dispersed.

[0025] The one-step method is suitable for solutions with lower viscosity, but since the viscosity of SA aqueous solution is relatively high, it is difficult to disperse evenly. Therefore, this experiment adopts a two-step method to prepare SA / PCL emulsion. First, SA is dissolved in deionized water to prepare a certain concentration of SA aqueous solution, and then it is allowed to stand for degassing. Chloroform, SA aqueous solution and Span80 are homogenized in proportion at a speed of 7000r / min for 15min on a homogenizer. Then a certain mass of PCL is added (the ratio of PCL mass to the volume of SA aqueous solution is 1g:1ml, and the mass fraction of Span80 relative to PCL is 66%), and the mixture is placed on a constant temperature shaker for continuous homogenization for 12h. After PCL is completely dissolved, the homogenizer is homogenized at a speed of 7000r / min for 15min to obtain the desired spinning emulsion. .

[0026] 2. Preparation of SA / PCL composite fiber membrane by emulsion electrospinning The above solution or emulsion was subjected to electrospinning to prepare SA / PCL composite fiber membrane. The spinning solution flow rate was 0.65 ml / h, the spinning voltage was 10.5 kV, the receiving distance was 10 cm, the spinning environment temperature was (25±5)°C, and the relative humidity was (60±5)%.

[0027] Preparation method of PCL / alginate (SA) membrane 2: 1. Preparation of SA / PCL emulsion 3.6% PCL and 2.4% SA were dissolved in TFE and stirred continuously for 24 h. ICA and MXF were added to the polymer solution at a mass ratio of 0.05 and 5 wt%, respectively, and stirred for 24 h to prepare electrospinning solutions containing the corresponding drugs. The solutions containing ICA and MXF were assembled into PCL / alginate (SA) membranes by electrospinning.

[0028] 2. Preparation of SA / PCL composite fiber membrane by electrospinning The electrospinning solution containing ICA was fed through a blunt needle at a rate of 1.0 mL h−1. The optimal voltage was 22 kV, the distance between the needle and the grounded mandrel was 20 cm, and the rotation speed was 500 rpm. The electrospinning was terminated after 4 h at 25 °C, and the solution containing MXF was electrospun for another 4 h under the same electrospinning parameters, which was labeled as SA / PCL composite fiber membrane.

[0029] 3. Characterization of SA / PCL composite fiber membrane The morphology of the electrospun nanofiber membrane was characterized by scanning electron microscopy (Hitachi S4800, Japan). 100 fibers and 100 pores formed between physically stacked fibers were randomly selected from the image and measured using Image J software to obtain the average diameter of the fiber and the average pore size of the corresponding membrane layer, ensuring that the pores were less than 1 μm so that bacteria and the like could not enter. The apparent density and porosity of the membrane were measured and calculated according to the methods studied in the previous article. The crystalline structure of MXF powder, ICA powder and electrospun fiber membrane was characterized by an X-ray diffractometer (D / Max, Rigaku, Japan), and the dispersion and crystallization of drugs in nanofibers were studied. The X-ray diffraction (XRD) experiment was performed with a scanning rate of 10°min-1 and a scanning range of 5°~70°.

[0030] (2) Multifunctional materials and preparation of alginate Preparation and properties of bioactive glass / nano-ZnO / alginate dressing 1. Preparation of bioactive glass by sol-gel method Nano bioactive glass (composition of 35CaO-60SiO2-5P2O5, mol%) was prepared by sol-gel combined freeze drying method. The experimental flow chart is shown in Figure 2. The specific experimental steps are as follows: 12.2mLTEOS and 7.8gCa(NO3)2·4H2O were added to a solution of 120mL deionized water and 40mL anhydrous ethanol. The pH value of the solution was adjusted to about 2 with hydrochloric acid under high-speed stirring. Then 1.3g of (NH4)2HPO4 was dissolved in deionized water. After it was completely dissolved, a certain amount of polyethylene glycol (PEG-10000) was added. After being fully stirred, it was slowly poured into the above solution and ammonia water was added to adjust the pH to 10. It was stirred for 48h and then placed in the air for aging for 24h to obtain a white precipitate. The precipitate was placed in a freeze dryer for freeze drying and then placed in a box-type electric furnace for heat treatment. The sintering temperature was 650°C to obtain nano-scale bioactive glass, which was recorded as BG. The absorption spectrum of the samples was measured by Fourier transform infrared spectrometer (FT-IR) to qualitatively analyze the composition of the materials, the microscopic morphology was observed by a field emission scanning electron microscope, the chemical composition was determined by an elemental electron spectrometer (EDS) attached to the scanning electron microscope, the particle size and particle size distribution were determined by a laser particle size analyzer, the sintering temperature of the bioactive glass was determined by thermogravimetric-differential thermal analysis using a differential scanning calorimetric analytical balance, and the structure of the micro-nano material was determined by XRD spectrum analysis.

[0031] 2. Preparation and characterization of zinc oxide nanoparticles Spherical ZnO nanoparticles were synthesized by mixing 0.1M zinc acetate dihydrate and 0.025~0.2M sodium hydroxide in methanol. During the synthesis, polyethylene glycol (PEG) was used as a surfactant and the reaction mixture was vigorously stirred at room temperature for 20 minutes. The amount of PEG added per gram of ZnO was selected to obtain a near monolayer coverage on the 40nm sized nanoparticles. A rough calculation shows that this is equivalent to 0.1g of PEG per gram of ZnO. It has been reported in the literature that PEG molecules are connected to ZnO through hydrogen bonds. In this case, the PEG molecule with an average molecular weight of 8000 has a chain length of *87nm. The average surface area of ​​a molecule of this length is about 19nm 2 The surface area of ​​a 40nm ZnO particle is about 500nm. 2 , so about 25 molecules of PEG are needed to provide complete surface coverage. This is equivalent to about 0.1gPEG per gram of ZnO. In order to remove the by-product (sodium acetate), the precipitate was washed several times with ethanol and deionized water, and then redispersed in deionized water using ultrasound. The UV absorption spectrum of nano-ZnO was measured in the range of 350~450nm using a PerkinElmer UV spectrophotometer. The average particle size of nano-ZnO was determined by NICOMP380ZLS dynamic light scattering (DLS). X-ray diffraction (XRD) analysis was performed using PANalyticalXPERTPRO to determine the characteristic peaks of nano-ZnO. The particles were analyzed continuously at 2° with a time interval of 0.02.

[0032] 3. Hydrophobic modification of calcium alginate fiber According to the important parts, 2-5 parts by weight of sodium alginate, 0.5-1 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and 0.5-1 parts by weight of N-hydroxysuccinimide are added in a certain molar ratio to 100-200 parts by weight of a phosphate buffer solution with a pH of 6-7, stirred evenly, and then added to 50-100 parts by weight of a methanol solution containing dodecylamine, stirred at room temperature for 12-24 hours, then precipitated with methanol, centrifuged, dissolved with distilled water, dialyzed for 48-96 hours, and freeze-dried to obtain hydrophobically modified sodium alginate.

[0033] 4. Wet spinning Sodium alginate is completely dissolved in distilled water to form a 10%~15% alginate solution (spinning solution), the spinning solution is poured into a syringe, the other end of which is connected to a nitrogen bottle, and squeezed into a 5%~10% calcium chloride solution (coagulation bath) under nitrogen pressure. The gel-like fiber derived from the coagulation bath is stretched, washed, wound, and dried to obtain calcium alginate fiber.

[0034] 5. Preparation of bioactive glass / nano-ZnO / alginate wound repair dressing The bioactive powder was added to a mixture of water and ethanol (volume ratio of 1:1), and the powder was evenly dispersed to form a suspension; ZnO nanoparticles with a concentration of 0.5% were mixed with the suspension to make them evenly dispersed. The hydrophobically modified calcium alginate fiber was immersed in saturated KMnO4 for 5-10 minutes, and then washed with distilled water to obtain a de-roughened alginate fiber; the de-roughened alginate fiber was immersed in the suspension and fully soaked, and the suspension was evenly sprayed on the fiber surface, and then centrifuged for dehydration. The obtained wet fiber was immersed in an ethanol solution, the ethanol was removed by centrifugation, and it was naturally dried, and then vacuum dried at 60-80℃, and then the dried fiber was cut into short fibers, and sterilized after non-woven fabric processing technology.

[0035] Preparation and properties of bioactive glass (SGBG) / chitosan / alginate dressing 1. Preparation of sol-gel bioactive glass (SGBG) powder solution Under stirring conditions at room temperature, prepare the hydrochloric acid (catalyst) aqueous solution required for the experiment. The molar percentage of the chemical composition of the prepared SGBG is: 60% SiO2, 36% CaO, 4% P2O5. Calculate the required volume or mass of triethyl phosphate (TEOS), tetraethyl orthosilicate (TEP), and calcium nitrate tetrahydrate (CN) as precursor raw materials for silicon, phosphorus, and calcium in proportion. For example, the precursors required to prepare 0.1mol of bioactive glass are: 12.5gTEP, 8.5gCN, 1.46gTEOS. Slowly drop TEOS and TEP into the hydrochloric acid aqueous solution drop by drop in sequence. Continue stirring for 1h after the addition is completed, then slowly add solid CN to the solution in multiple times. Continue stirring the solution after the addition is completed to fully hydrolyze the precursors, and stop when the solution becomes transparent and uniform. The obtained sol solution was aged at room temperature for 3 days, so that the molecules in the sol solution continued to undergo polycondensation reaction until gelation formed a large piece of wet gel. The gel was dried at 60℃ and 120℃ for 3 days respectively to remove a large amount of ethanol byproducts produced by the reaction. The dried gel was placed in a high-temperature sintering furnace for sintering (sintering conditions: heating rate 1℃ / min; heating from room temperature to 600℃ at 350℃ and 600℃ for 120min each). The sintered product, agate grinding balls, and anhydrous ethanol were loaded into a ball mill at a mass ratio of 1:3:1 and ball milled on a ball mill (ball milling parameters: 672rmp / min, 4h). After the ball milling, the ball milling liquid was placed in a 120℃ oven for one day to remove ethanol and obtain smaller-scale bioactive glass particles. The obtained powder was sieved with a 20-50 micron standard sieve to obtain SGBG powder. The bioactive glass powder is dispersed in acetone at a solid-liquid ratio of 80-150 g / 200-500 ml, and ultrasonic oscillation and mechanical stirring are applied to obtain a bioactive glass dispersion.

[0036] The crystal phase composition of SGBG powder was characterized by X-ray diffraction analyzer, and the test and analysis were carried out at a scanning rate of 10° / min and a 2θ diffraction angle scanning range of 10~70°. FTIR was used to characterize the chemical structure of SGBG powder. The sample was prepared by tableting method. The SGBG powder to be tested and KBr powder were evenly ground in a ratio of 1:100, pressed into tablets and dried. The obtained tablets can be placed in the instrument for detection. The surface morphology of SGBG powder particles was observed by field emission scanning electron microscopy (GeminiSEM). After ultrasonically dispersing an appropriate amount of SGBG powder in an ethanol solution, the upper layer of solution was dripped on a sample table with a copper sheet. After drying and gold spraying, the sample table was placed in GeminiSEM for observation and photography.

[0037] 2. Preparation of Sodium Alginate Solution Containing Chitosan and Bioactive Glass (SGBG) Prepare an acetic acid aqueous solution containing chitosan (the ratio of the mass of chitosan to the volume of the acetic acid aqueous solution is (1-3) g: 100 mL); evenly mix the acetic acid aqueous solution containing chitosan and the sodium alginate aqueous solution (the mass fraction of acetic acid in the acetic acid aqueous solution is 1%; the sodium alginate aqueous solution is prepared by mixing sodium alginate and ultrapure water, and the ratio of the mass of sodium alginate to the volume of ultrapure water is (0.5-1.5) g: 50 mL); then add the bioactive glass suspension aqueous solution to obtain a mixture (the bioactive glass suspension is prepared by mixing bioactive glass and ultrapure water; the ratio of the mass of bioactive glass to the volume of ultrapure water is (0.2-0.6) g: 2 mL).

[0038] 3. Preparation of bioactive glass (SGBG) / chitosan / alginate dressing The sodium alginate spinning solution is used to make silk, the silk is drawn and cleaned, and then soaked in a solution or suspension containing a wound healing promoting drug, and then dried, wound and cut into sodium alginate fibers; the sodium alginate fibers are opened, combed, and reinforced with needle punching or hydroentanglement with or without cross-laying to obtain the sodium alginate dressing.

[0039] ATR-FTIR was used to detect sodium alginate fibers doped with different SGBG contents, and qualitative analysis was performed to determine whether SGBG powder was successfully incorporated into the fibers. A synchronous thermal analyzer was used to detect the thermal stability of the fibers and the actual content of SGBG therein. Test conditions (atmosphere: air; heating rate: 10°C / min; heating range: 30°C to 700°C). The fibers containing SGBG powder were immersed in simulated human body fluid (SBF) for 12 hours, 1 day, 3 days, and 5 days, respectively. After centrifuging the immersion liquid, the supernatant was taken, and the concentrations of Ca, Si, and P ions in the extract were detected using the ICP-AES method.

[0040] Preparation and properties of copper-containing mesoporous bioactive glass / honey / alginate dressing 1. Synthesis and material characterization of Cu-MBGs Synthesis of MBGs (SiO2-CaO-P2O5-CuO): After some modification, the EISA method was used for synthesis. Tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and copper (II) nitrate hemihydrate (pentahydrate) were dissolved in ethanol / water to form a sol. Hydrochloric acid was used as a catalyst, and Pluronic F108 was added to the sol as a structure directing agent. In a typical synthesis, 6.92 g F108 (Mw = 14600, Sigma) was dissolved in 36.2 ml ethanol (99.9%) in a 40 ° C water bath to obtain solution (I), 2.48 g Ca (NO3) 24H2O, 0.637 g TEP (99.8%), 11.66 g TEOS, 1.9 ml 1M HCl, 15.24 ml ethanol and 5.72 ml H2O were fully mixed under stirring to obtain solution (II). Solution (I) and solution (II) were mixed in a bottle and stirred in a sealed container overnight in a 40°C water bath. The sol was then cast in a Petri dish and treated with EISA in a room temperature water bath at 40°C. The resulting gel was placed at 40°C for 6 days to age. The collected dry gel was then calcined at 600°C for 5 hours to remove the structure directing agent and nitrate. The resulting sample was recorded as MBGSi80 (molar ratio Si / Ca / P=80 / 15 / 5). MBGSi78Cu2 (molar ratio Si / Cu / Ca / P=78 / 2 / 15 / 5) and MBGSi75Cu5 (molar ratio Si / Cu / Ca / P=75 / 5 / 15 / 5) were synthesized, and the molar ratio of Ca / P remained the same as when MBGSi80 was synthesized, but the molar numbers of TEOS and Cu(NO3)22.5H2O were adjusted to match the set ratio of CuO substituted in the glass composition. After calcination, all MBGs were ground using a benchtop planetary ball mill (MinMill, Philips) to obtain fine powders of MBGs.

[0041] Powder X-ray diffraction (XRD) was performed using a position-sensitive Huber G670 detector and copper Ka1 radiation (k = 1.54060 Å). The morphology was characterized by transmission electron microscopy (TEM; JEM-1400 Plus, JEOL, Peabody, MA) operating at 120 kV. Small-angle X-ray scattering (SAXS) was performed on a Kratky compact small-angle system (Hecus, Austria). The system was equipped with a position-sensitive detector (PSD50M) consisting of 1024 channels, each with a width of 55.5 lm. The structural properties of MBGs were determined by N2 physical adsorption at 77 K using an ASAP2010 absorptometer (Micrometrics Co, Norcross, GA). The specific surface area and pore size distribution were determined by the brunauer-emmet-teller (BET) method and the Barrett-Joyner-Halenda (BJH) method, respectively. The total pore volume was calculated from the amount of adsorbed nitrogen at P / P0=0.98.

[0042] 2. Preparation of honey powder By weight, 50-100 parts of honey are decrystallized and liquefied at 65-80°C, and then low-temperature dehydrated to a water content of 15%-25% of the honey, and then 0.5-3 parts of synthetic borneol are added to stir and mix them thoroughly, and the mixture is placed in a freeze dryer for freeze drying at -40--10°C for 12-36 hours, and then taken out to form solid honey, and then the solid honey layer is crushed into 60-500 mesh honey powder.

[0043] 3. Preparation of functional alginate dressing The reagents used were sodium alginate (Exodo-Científica, 90.8 ~ 106%), anhydrous calcium chloride (Neon-96%~ 101%), sodium carboxymethylcellulose (Dinamica-100%) and double distilled glycerol (MV-Química, USP grade). The concentration used in the dressing was determined to be 100 mg / ml based on the results of the minimum bactericidal concentration of bioactive glass.

[0044] First, Cu-MBGs were gradually added to distilled water, and the suspension was dispersed in an ultrasonic probe (Ecosonics) for 2 min. A certain volume of honey was added to the solution containing Cu-MBGs to determine the honey concentration ((0%, 5%, 10%, 15%, 20% (v / v))). Subsequently, the honey / SA / PVA mixture was stirred at room temperature for 12 h to obtain a homogeneous solution.

[0045] Separate solutions of CMC and alginate were prepared at 1.5% (w / v) in distilled water. Both solutions were kept at 50°C under magnetic stirring (Fisatom) until the mixture was homogenized within 30 min. Glycerol was added to each solution at 5%, 7.5% and 10% (w / v), respectively. Glycerol acts as a plasticizer and is necessary to obtain a soft dressing. At low concentrations, it results in a brittle dressing, while at high concentrations it promotes high elasticity. But it has a sticky appearance, making it difficult to handle. A 1% aqueous solution of CaCl2 (0.05 g of calcium chloride per 1 g of alginate) was prepared and dropped into the alginate solution while it was still stirred and heated.

[0046] After obtaining the two membrane solutions, they were mixed in a 1:1 ratio (mass) for 30 min under mechanical stirring with a marine propeller (Fisatom) at 900 rpm. The solutions were then poured into an acrylic plate at a standard concentration of 0.28 g / cm2 and kept in a circulating air oven (CIENLAB) at 40°C for 24 h.

[0047] After the solution has dried, the resulting dressing needs to undergo a second step, cross-linking. Soak in an aqueous solution of 5% calcium chloride and 3% glycerol for 20 minutes; then wash the dressing by soaking it in a 3% glycerol aqueous solution for 1 minute. Once the optimal glycerol concentration has been determined, a new functional dressing is prepared using the previous method, but varying the amount of CaCl2 in the solution, using 25%, 50%, and 75% of the amount previously described. This agent is associated with the stiffness, tensile strength, and deformation of the dressing.

[0048] (3) Materials and preparation of unidirectional moisture-conducting layer 1. Preparation of PCL solution PCL (Mw≈80000 g / mol) was purchased from Sigma-Aldrich, USA. Medical acetone was purchased from Nanjing Baker Trading Co., Ltd. (Nanjing, China). All solvents were of analytical grade and no further purification was required. PCL was dissolved in medical acetone at a mass fraction of 1:4 and stirred at room temperature for 4 h using a magnetic stirrer to obtain a solution.

[0049] 2. Spinning parameters of electrospinning During the electrospinning process, the solutions were poured into 5 ml syringes and installed on the electrospinning equipment for spinning. A blue needle with an inner diameter of 0.41 mm was used, the spinning voltage was 15 kV, the flow rate was 1 mL / h, the distance between the needle and the collector was 15 cm, and a rotating drum at 300 rpm was used as the collector. The prepared samples were dried in a drying oven and stored in a refrigerator at 4 °C.

[0050] 3. Characterization of PCL membrane The morphology of the material was characterized by scanning electron microscopy (Gemini SEM 300, Carl Zeiss AG), and the average diameter of the obtained fibers was analyzed by a nanometer. The organic composition of the fibers was detected by a Fourier transform infrared spectrometer (FTIR, Thermo Scientific Nicolet iN10), and the hydrophobicity of the material was measured by a static contact angle tester (WCA, SA100). Its thermal stability was measured by a thermogravimetric analyzer (TGA, TA-Q500).

[0051] (4) Hot pressing combined process In the process of laminating the electrospun membrane and non-woven fabric using a temperature and pressure controlled laminating device, the materials are placed in the structural order of "antimicrobial barrier layer, alginate functional layer and unidirectional moisture conducting layer". During the laminating process, the equipment is set to work at a laminating temperature of 56°C and a pressure of 12N. Such temperature and pressure settings are to ensure that the three layers of materials can be effectively combined without being burned, while maintaining the inherent properties of the materials. The laminating time is controlled at 40 seconds to ensure that the interface between the materials can be fully fused without causing the material performance to deteriorate due to excessive laminating time.

[0052] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the scope of the present invention shall be included in the protection scope of the present invention.

Claims

1. An anti-infection and healing-promoting alginate dressing, characterized in that: It includes an antibacterial barrier layer, an alginate multifunctional layer, and a one-way moisture conducting layer; The antibacterial barrier layer is prepared by the following method: 1) SA was dissolved in deionized water to prepare a SA aqueous solution of a certain concentration, and the solution was allowed to stand for degassing. Chloroform, SA aqueous solution and Span80 were homogenized in a homogenizer at a speed of 7000 r / min for 15 min according to the proportion, and then PCL was added. The solution was placed on a constant temperature shaker for continuous homogenization for 12 h. After PCL was completely dissolved, the homogenizer was homogenized at a speed of 7000 r / min for 15 min to obtain a spinning emulsion. The ratio of PCL mass to SA aqueous solution volume was 1 g: 1 ml, and the mass fraction of Span80 relative to PCL was 66%. 2) The emulsion is subjected to electrospinning to prepare a SA / PCL composite fiber membrane; wherein the spinning solution flow rate is 0.65 ml / h, the spinning voltage is 10.5 kV, the receiving distance is 10 cm, the spinning environment temperature is 25±5° C., and the relative humidity is 60±5%; The unidirectional moisture conducting layer is prepared by the following method: A) PCL was dissolved in medical acetone at a mass fraction of 1:4 and stirred at room temperature for 4 h using a magnetic stirrer to obtain a solution; B) Electrospinning was performed on it. During the electrospinning process, the solutions were poured into 5 ml syringes respectively and installed on the electrospinning equipment in turn for spinning; a needle with an inner diameter of 0.41 mm was used, the spinning voltage was 15 kV, the flow rate was 1 mL / h, the distance between the needle and the collector was 15 cm, and a rotating drum at 300 rpm was used as the collector; the prepared samples were dried in a drying oven and stored in a refrigerator at 4°C.

2. An anti-infection and healing-promoting alginate dressing according to claim 1, characterized in that: The alginate multifunctional layer is a bioactive glass / nano ZnO / alginate dressing, and the bioactive glass / nano ZnO / alginate dressing is prepared by the following method: A) Add 12.2 mL of LTEOS and 7.8 g of Ca(NO3)2·4H2O to a solution of 120 mL of deionized water and 40 mL of anhydrous ethanol, adjust the pH value of the solution to 1.8-2.2 with hydrochloric acid while stirring, then dissolve 1.3 g of (NH4)2HPO4 in deionized water, add polyethylene glycol (PEG-10000) after it is completely dissolved, stir well and pour into the above solution, add ammonia water to adjust the pH to 10, stir for 48 h, then place in air for aging for 24 h to obtain a white precipitate, place the precipitate in a freeze dryer for freeze drying, and then place it in a box-type electric furnace for heat treatment at a sintering temperature of 650°C to obtain nanoscale bioactive glass; B) Spherical ZnO nanoparticles were synthesized by mixing 0.1 M zinc acetate dihydrate and 0.025-0.2 M sodium hydroxide in methanol. During the synthesis, polyethylene glycol was used as a surfactant and the reaction mixture was stirred at room temperature for 20 min, wherein the amount of PEG added was 0.08-0.12 g PEG per gram of ZnO. The precipitate was washed several times with ethanol and deionized water, and then redispersed in deionized water using ultrasound. C) According to the weight ratio, 2-5 parts by weight of sodium alginate, 0.5-1 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and 0.5-1 parts by weight of N-hydroxysuccinimide are added in a certain molar ratio to 100-200 parts by weight of a phosphate buffer solution with a pH of 6-7, stirred evenly, and then added to 50-100 parts by weight of a methanol solution containing dodecylamine, stirred at room temperature for 12-24 hours, then precipitated with methanol, centrifuged, dissolved with distilled water, dialyzed for 48-96 hours, and freeze-dried to obtain hydrophobically modified sodium alginate; D) Sodium alginate is completely dissolved in distilled water to form a 10% to 15% alginate solution as a spinning solution, the spinning solution is poured into a syringe, the other end of which is connected to a nitrogen bottle, and squeezed into a 5% to 10% calcium chloride solution under nitrogen pressure for a coagulation bath, and the gel-like fibers derived from the coagulation bath are stretched, washed, wound, and dried to obtain calcium alginate fibers; E) Adding bioactive glass to a mixture of water and ethanol, and uniformly dispersing the powder to form a suspension, wherein the volume ratio of water to ethanol in the mixture is 1:1; mixing ZnO nanoparticles with a concentration of 0.5% with the suspension to uniformly disperse the particles; immersing hydrophobically modified calcium alginate fibers in saturated KMnO4 for 5-10 minutes, and then washing with distilled water to obtain de-roughened alginate fibers; immersing the de-roughened alginate fibers in the suspension and fully soaking them, and uniformly spraying the suspension on the fiber surface, and then centrifuging and dehydrating the fibers, soaking the obtained wet fibers in an ethanol solution, centrifuging to remove the ethanol, drying them naturally, and then vacuum drying them at 60-80°C, and then cutting the dried fibers into short fibers, sterilizing them after a non-woven fabric processing process.

3. An anti-infection and healing-promoting alginate dressing according to claim 1, characterized in that: The alginate multifunctional layer is a bioactive glass / chitosan / alginate dressing, and the bioactive glass / chitosan / alginate dressing is prepared by the following method: A) Take 12.5g TEP, 8.5g CN, and 1.46g TEOS, and drop TEOS and TEP into a hydrochloric acid aqueous solution in sequence, continue stirring for 1h after the addition is complete, and then add solid CN to the solution in multiple portions, continue stirring the solution after the addition is complete to fully hydrolyze the precursor, and stop when the solution becomes transparent and uniform; The obtained sol solution was aged at room temperature for 3 days, and the gel was dried at 60°C and 120°C for 3 days respectively; the dried gel was placed in a high-temperature sintering furnace for sintering; the obtained sintered product, agate grinding balls, and anhydrous ethanol were loaded into a ball mill at a mass ratio of 1:3:1 and ball milled on a ball mill; after the ball milling, the ball milling liquid was placed in a 120°C oven for drying for one day; the obtained powder was sieved with a 20-50 micron standard sieve to obtain SGBG powder; the SGBG powder was dispersed in acetone at a solid-liquid ratio of 80-150 g / 200-500 ml, and ultrasonic vibration and mechanical stirring were applied to obtain a bioactive glass dispersion; B) preparing an acetic acid aqueous solution containing chitosan, wherein: the ratio of the mass of chitosan to the volume of the acetic acid aqueous solution is 1-3 g:100 mL; uniformly mixing the acetic acid aqueous solution containing chitosan and a sodium alginate aqueous solution, wherein: the mass fraction of acetic acid in the acetic acid aqueous solution is 1%, the sodium alginate aqueous solution is prepared by mixing sodium alginate and ultrapure water, and the ratio of the mass of sodium alginate to the volume of ultrapure water is 0.5-1.5 g:50 mL; then adding an aqueous solution of a bioactive glass suspension to obtain a mixture, wherein: the bioactive glass suspension is prepared by mixing bioactive glass and ultrapure water, and the ratio of the mass of the bioactive glass to the volume of the ultrapure water is 0.2-0.6 g:2 mL; C) The spinning solution of sodium alginate is used to make silk, the silk is drawn and washed, and then soaked in a solution or suspension containing a wound healing promoting drug, and then dried, wound and cut into sodium alginate fibers, and the sodium alginate fibers are opened, combed and reinforced with needle punching or hydroentanglement with or without cross-lapping.

4. The anti-infection and healing-promoting alginate dressing according to claim 3, characterized in that: The sintering conditions in step a) are: heating rate 1°C / min; during heating from room temperature to 600°C, keeping at 350°C and 600°C for 120 min each; ball milling parameters: 672 rpm, 4 h.

5. An anti-infection and healing-promoting alginate dressing according to claim 1, characterized in that: The alginate multifunctional layer is a copper-containing mesoporous bioactive glass / honey / alginate dressing, and the copper-containing mesoporous bioactive glass / honey / alginate dressing is prepared by the following method: A) 6.92 g of Pluronic F108 was dissolved in 36.2 ml of ethanol in a water bath at 40°C to obtain solution I, 2.48 g of Ca(NO3)24H2O, 0.637 g of TEP, 11.66 g of TEOS, 1.9 ml of 1 M HCl, 15.24 ml of ethanol and 5.72 ml of H2O were fully mixed under stirring to obtain solution II; solution I and solution II were mixed in a container, and stirred in a sealed container in a water bath at 40°C overnight; the sol was then poured into a petri dish and subjected to EISA treatment in a water bath at room temperature of 40°C; the obtained gel was placed at 40°C for 6 days to age; the collected dry gel was then calcined at 600°C for 5 hours, and then ground using a desktop planetary ball mill to obtain MBGs fine powder; B) by weight, 50-100 parts of honey are decrystallized and liquefied at 65-80°C, and then low-temperature dehydrated until the water content of the honey is 15%-25%, and then 0.5-3 parts of synthetic borneol are added to stir and mix well, and the mixture is placed in a freeze dryer for freeze drying at -40--10°C for 12-36 hours, and then taken out to form solid honey, and then the solid honey layer is crushed into honey powder of 60 meshes to 500 meshes; C) MBGs fine powder was gradually added to distilled water, the suspension was dispersed in an ultrasonic probe for 2 min, honey was added to it, and subsequently, the honey / SA / PVA mixture was stirred at room temperature for 12 h to obtain a homogeneous solution; 1.5% w / v CMC and alginate separation solutions were prepared in distilled water; the two solutions were kept at 50 °C under magnetic stirring until the mixture was homogenized within 30 min; 5%, 7.5% and 10% w / v glycerol were added to each solution respectively; 1% CaCl2 aqueous solution was prepared and dropped into the alginate solution while it was still stirred and heated; after obtaining the two membrane solutions, they were mixed at a mass ratio of 1:1 under mechanical stirring at 900 rpm for 30 min; then the solutions were heated at 0.28 g / cm 2 The solution was poured into an acrylic plate under standard conditions and kept in a circulating air oven at 40°C for 24 hours; after the solution dried, the obtained dressing was immersed in an aqueous solution of 5% calcium chloride and 3% glycerol for 20 minutes; the dressing was then immersed in a 3% glycerol aqueous solution for 1 minute for washing.

6. The anti-infection and healing-promoting alginate dressing according to claim 5, characterized in that: In step a), the Si:Ca:P molar ratio of the MBGs fine powder is 80:15:

5.

7. The anti-infection and healing-promoting alginate dressing according to claim 5, characterized in that: In step A), solution II also contains copper (II) nitrate hemihydrate (pentahydrate), and the obtained MBGs fine powder has a Si:Cu:Ca:P molar ratio of 78:2:15:5 or 75:5:15:

5.

8. An anti-infection and healing-promoting alginate dressing according to claim 1, characterized in that: The anti-infection and healing-promoting alginate dressing is prepared by the following method: laminating the electrospun membrane and the non-woven fabric using a temperature and pressure controllable laminating device, and during the lamination process, placing the materials in the structural order of an antimicrobial barrier layer, an alginate functional layer, and a unidirectional moisture conducting layer; During the lamination process, the equipment was set to work at a lamination temperature of 56°C and a pressure of 12N, and the lamination time was controlled at 40 seconds.

9. An anti-infection and healing-promoting alginate dressing according to claim 1, characterized in that: The preparation method of the antibacterial barrier layer is replaced by the following method: 1) 3.6% PCL and 2.4% SA were dissolved in TFE and stirred continuously for 24 h. ICA and MXF with a mass ratio of 0.05 and 5 wt% were added to the polymer solution, respectively, and stirred for 24 h to prepare an electrospinning solution containing the corresponding drugs. Solutions containing ICA and MXF were assembled into PCL / alginate membranes by electrospinning, respectively; 2) The electrospinning solution containing ICA was heated at 1.0 mL h −1 The material was fed through a blunt needle at a rate of 22 kV; the voltage was 22 kV, the distance between the needle and the grounded mandrel was 20 cm, and the rotation speed was 500 rpm; at 25 °C, the electrospinning was terminated after 4 h, and the solution containing MXF was electrospun for another 4 h under the same electrospinning parameters.

Citation Information

Patent Citations

  • Alginate composite antibiotic dressing and the preparation method

    CN106267309A

  • Alginate wound surface restoring dressing and preparation method thereof

    CN107899061A

  • Preparation method of medical foam dressing with slow-release antibacterial effect

    CN110433321A

  • Porous structure hemostatic fiber material and preparation method thereof

    CN112981554A

  • Bionic asymmetric sponge dressing and preparation method thereof

    CN115154642A